Disability Insurance Benefits and Labor Supply: Some Additional Evidence - Campolieti, Michele (Journal of Labor Economics, 2004)
This article examines the effects of a change in the Canada/Quebec Pension Plan (C/QPP) disability benefits on the labor supply of older Canadian workers. I obtain my estimates by exploiting a large increase in benefits that only occurred in the QPP program, which only operates in Quebec, while benefits in the CPP program, which operates in the rest of Canada, were unaffected. Unlike the existing estimates from the United States, as well as earlier Canadian obtained by Gruber, I find that disability benefits are not associated with a large increase in the nonparticipation of older men.